Calculus: Early Transcendentals (2nd Edition)

Published by Pearson
ISBN 10: 0321947347
ISBN 13: 978-0-32194-734-5

Chapter 8 - Sequences and Infinite Series - 8.3 Infinite Series - 8.3 Exercises - Page 623: 25


$=\dfrac {e^{2}}{e^{2}-1}$

Work Step by Step

$\sum ^{\infty }_{k=1}e^{-2n}=\sum ^{\infty }_{k=1}\left( e^{-2}\right) ^{k}=\dfrac {a_{1}}{1-r};a_{1}=e^{-2};r=e^{-2}\Rightarrow S_{\infty }=\dfrac {e^{-2}}{1-e^{-2}}=\dfrac {e^{2}}{e^{2}-1}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.